2022
DOI: 10.1055/s-0042-1756684
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Anemic Effects of Ethanol Leaf Extracts of Mucuna poggei and Telfairia occidentalis in Phenyl-Hydrazine-Induced Anemia in Wistar Albino Rats

Abstract: Introduction With the use of recent therapeutic data, several methods for finding medications from untapped natural materials continue to advance research and development. The antioxidant and antianemic effects of ethanol leaf extracts of Telfairia occidentalis and Mucuna poggei in phenylhydrazine-induced anemia in Wister albino rats were investigated. Method A total of 54 male albino rats were randomly assigned to nine experimental groups (n = 6). Anemia was induced in groups 2 to 9 with 10 mg/kg bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Hb plays a pivotal role as the respiratory pigment within RBCs, and intravascular hemolysis of RBCs leads to the release of hemoglobin and the accumulation of free heme . Moreover, it has been established that phenylhydrazine can bind to erythropoietin receptors, a hormone that regulates hematopoiesis and promotes erythrocyte production . PC-Ext contains substances capable of acting similarly to erythropoietin by binding to its receptors, potentially competing with PhZ, or using an alternative mechanism to stimulate erythrocyte production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hb plays a pivotal role as the respiratory pigment within RBCs, and intravascular hemolysis of RBCs leads to the release of hemoglobin and the accumulation of free heme . Moreover, it has been established that phenylhydrazine can bind to erythropoietin receptors, a hormone that regulates hematopoiesis and promotes erythrocyte production . PC-Ext contains substances capable of acting similarly to erythropoietin by binding to its receptors, potentially competing with PhZ, or using an alternative mechanism to stimulate erythrocyte production.…”
Section: Discussionmentioning
confidence: 99%
“… 50 Moreover, it has been established that phenylhydrazine can bind to erythropoietin receptors, a hormone that regulates hematopoiesis and promotes erythrocyte production. 51 PC-Ext contains substances capable of acting similarly to erythropoietin by binding to its receptors, potentially competing with PhZ, or using an alternative mechanism to stimulate erythrocyte production. Furthermore, the partial or complete restoration of MCV and MCHC suggests that parsley facilitates the normalization of erythrocyte size and hemoglobin content, indicative of enhanced cell multiplication and normal hemoglobin synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…19 The catalase activity was determined by the method of Beers and Sizer. 20 The reduced glutathione in the tissue was determined by the method of Moron et al 21 The malondialdehyde of the tissue was determined as earlier reported by Udeozor et al 22…”
Section: Oxidative Stress Indicatorsmentioning
confidence: 99%
“…The CAT activity was assayed according to the method described by Udeozor et al 27 . In brief, 2.5 mL of phosphate buffer and 2 mL of H 2 O 2 were added to the test tube exactly at the same times.…”
Section: Determination Of Catalase (Cat) Activitymentioning
confidence: 99%